Transinformação – v. 26, n. 3 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
Link de acesso ao Número:http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/issue/view/300